Zakah and Waqf for Cryptocurrency in Islamic Law - Bintarto, Muhammad Al Ikhwan; Setiawan, Yudi; Alqarni, Muhammad Uwais; Hilmi, Faishal (AL-ISTINBATH : Jurnal Hukum Islam, 2022)
Cryptocurrency is a virtual currency based on block chain. Yet, some countries forbid it as a means of payment in transactions. It can only be used as diversification in investment. In fact, cryptocurrency is a liquid asset even though it fluctuates. In Islam, there are different views whether cryptocurrency can be assets or can be zakah, infaq, sadaqah, and waqf. The object of this study is to answer whether the crypto can be al-amwal azzakawiyah or something that can be zakah and waqf which can be maslahah for the society. Another purpose of this research is to enlighten about zakah and waqf managers on what cryptocurrency is for. The theory used is the theory of zakah and waqf in Islam. This is a qualitative study with a conceptual approach and an Islamic law approach. The result of this research is that cryptocurrency can be said as wealth or al-maal that can be zakah, infaq, and waqf because it has fulfilled several requirements to be classified as wealth or al-maal in Islam.Â  Zakah calculation of crypto currency must exceed the nisab 2,5% equivalent to 85 grams of gold, the owned can already be an object of zakah.